A Taylor rule for fiscal policy in a fixed exchange rate regime - Jesper Pedersen; Søren Hove Ravn (Danmarks Nationalbank, 2014)
We study fiscal policy in Denmark in the period 2004-2012 and compare the actual policy to counterfactual, rule-based alternatives. Given Denmark's fixed exchange rate towards the euro, it is the job of fiscal policymakers to stabilise fluctuations in output and inflation. However, we find that fiscal policy had the 'wrong sign' in the years leading up to the recent crisis, i.e. that fiscal policy contributed positively to the output gap when a contractionary policy was called for. In fact, our rule-based approach to fiscal policy would have prescribed a very substantial fiscal tightening by as much as 1.5 pct. of GDP in each of the years 2006-08. Furthermore, we show that even based on real-time data, which significantly underestimated the ongoing boom during those years, a substantial tightening of fiscal policy was called for. A tighter fiscal policy during the boom years would have helped Denmark avoid a large loss of competitiveness, thereby dampening and shortening the subsequent economic crisis in Denmark significantly, and could have made room for greater fiscal expansions during the crisis if desired.
Keywords: E17; E32; E62; E65; F41; 330; DSGE Models; Fiscal Policy; Fixed Exchange Rates; Real-Time Data